2017
DOI: 10.1108/mrr-04-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

HR analytics and performance appraisal system

Abstract: PurposeThis paper aims to explore the role of human resource (HR) analytics on employees’ willingness to improve performance. In doing so, the paper examines issues related to the performance appraisal (PA) system which affect employees’ willingness to improve performance and how HR analytics can be a potential solution to deal with such issues. Design/methodology/approachThe paper develops a conceptual framework along with propositions by integrating both academic and practitioner literatures, in the field of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…But according to a review, after examining literature, it found that student evaluation of teaching (SET) is not an excellent choice for summative evaluation [8]. A duo proposed that the use of HR analytics negatively associates with the subjective bias in the performance appraisal system [9]. In addition, conventional evaluation methods lack assigning weight to individual criteria and rely much on numerical values [10].…”
Section: Introductionmentioning
confidence: 99%
“…But according to a review, after examining literature, it found that student evaluation of teaching (SET) is not an excellent choice for summative evaluation [8]. A duo proposed that the use of HR analytics negatively associates with the subjective bias in the performance appraisal system [9]. In addition, conventional evaluation methods lack assigning weight to individual criteria and rely much on numerical values [10].…”
Section: Introductionmentioning
confidence: 99%
“…The result is that smaller businesses miss out on many of the benefits of HR analytics that are enjoyed by larger businesses. These benefits include employee development, employee retention, and higher competitiveness and productivity (Chaturvedi, 2016;Sharma & Sharma, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, HR analytics enables HR to become a strategic partner in organizational decision making. Studies on the impact of HR analytics have reported improvements in human capital management (Mihalcea, 2017), increased levels of employee productivity (Sharma & Sharma, 2017), higher return on human capital investment (Mihalcea, 2017), and workplace learning (Giacumo & Breman, 2016).…”
Section: Figure 1 14 Hr Metrics Examplesmentioning
confidence: 99%
See 2 more Smart Citations